Urdu Translation and Psychometric Validation of Manual Ability Measure (MAM-36) in Patients with Neurological Disease - Hafsa Mushtaq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The pathophysiological underpinnings of lifelong impairment in a variety of acute and chronic neurological illnesses include neuronal loss and destruction. Upon neuroaxonal injury, levels of neurofilament proteins rise in the blood and cerebrospinal fluid (CSF). The Manual Ability Measure (MAM-36) is a questionnaire about the perceived ease or difficulty individuals may experience when performing unilateral and bilateral ADL tasks. The objective o was to translate and validate the Urdu version of manual ability measure for patients with neurological disorders Methods: A standardized step by step forward and backward translation procedure was followed. Data was collected from 108 patients with neurological diseases. Researcher employed Urdu version of self-administered MAM-36 questionnaire for data collection. Data was analysed by using SPSS.25. in this study test retest reliability was found through alpha Cronbach and Intra class Coefficient and construct validity was assess in relation to MusiQOL Results: The reliability analysis of the Manual Ability Measure (MAM-36) questionnaire demonstrated a high level of internal consistency, with both readings having a Cronbach’s alpha reliability coefficient of 0.987. The sample consisted of 45 males (41.7%) and 63 females (58.3%), and the majority had a middle socioeconomic status (66.7%). Descriptive statistics showed that the sample had a mean age of 56±4 years, a mean height of 1.68±0.1 meters, a mean weight of 86.5±11.0 kg, a mean body mass index of 30.7±4, a mean grip strength of dominant hand of 24.6±1.9, and a mean grip strength of non-dominant hand of 22.9±0.7. Practical Implication: The reliability statistics indicate that the MAM-36 questionnaire is a reliable and valid tool for measuring manual ability in individuals with neurological diseases. The strong positive correlation between the variable of interest and the reference variable supports the construct validity of the measure. Conclusion: Hence it was concluded that, the reliability statistics indicate that the MAM-36 questionnaire is a reliable and valid tool for measuring manual ability in individuals with neurological diseases. The strong positive correlation between the variable of interest and the reference variable supports the construct validity of the measure. Keywords: Psychometric validation, Manual Ability Measure (MAM-36), Neurological disease